Influence of Time Dependent Material Properties in the Construction Stage Analysis of Composite Cable-Stayed Bridge - Mishra, Bhupendra Prasad (Far Western Review, 2025)
This study analyzes recent advancements in the erection analysis of cable-stayed bridges with composite steel–concrete decks, focusing on time-dependent effects during staged construction. While prior studies have addressed erection strategies, this work emphasizes the practical modeling of de-stressing and re-stressing operations using both backward and forward analysis methods. A parametric investigation quantifies the influence of creep and shrinkage on internal forces, showing that neglecting these effects can lead to camber deviations of up to 15 mm and cable force variations of 8–12%. The study demonstrates that incorporating accurate time-dependent material models is essential to control deflections and ensure structural performance. Findings reinforce the importance of detailed construction-stage analysis especially in cantilever erection methods to mitigate long-term deformation and associated economic implications. This research contributes practical insights for refining erection simulations and improving predictive accuracy in cable-stayed bridge design.